(untitled) (Damu Journal of Sport Sciences, 2025)
The research aims to shed light on these issues and provide recommendations that will enhance the role of organizational values ​​in developing administrative and educational performance within educational institutions, thus contributing to achieving educational goals more effectively. The research areas were from the point of view of the scouting division and stages officials in the General Directorates of Education in Iraq, for the period from 11/20/2024 to 2/4/2025 in the Directorate of Scouting Sports Activities in the General Directorates of Education in Iraq. The researcher adopted a percentage of (100%) and a comprehensive sample enumeration method, where (140) division and stage officials were approved, distributed among (20) education directorates affiliated with the Iraqi Ministry of Education, and who are continuing in official working hours for the year (2023/2024). The researcher recommended that the goals set by the directorates for the scouting stages should be clear and understood with great precision in order to achieve them correctly. The division and stage officials should work to set the correct path for the wooden badge holders through this to clarify the goals that must be implemented. Work to create a positive atmosphere in order to consolidate and improve the relationship between the division and stage officials and the wooden badge holders in the correct manner.